Action du fluor comme elemente polluant de l’eau de mer - Octavian, Șerbănescu; Mihnea, Radu; Cuingioglu, Elvira; Icmet, Bilal (Cercetări Marine - Recherches Marines, 2026)
In the present paper the authors establish the influence of the fluor ion resulted from a sulphuric acid and chemical fertilizer plant, on the marine flora and fauna. Owing to the different degrees of solubility of the fluor compounds, the laboratory experiments were carried out with calcium fluoride - (CaF2) - and with sodium fluoride - (NaF). The concentration of the respective solutions ranged between 2 and 100mg per liter. Observations were made on the behavior of various species of fish, mollusks and crustacea, in solutions of varying concentration.